Chemistry reaction rates and equilibrium (St. Louis : Coronet Films & Video)
Explain the factors that influence the rates of chemical reactions and also explore equilibrium, how it can be upset, and its role in the chemical industry
Copy available in DVD format
Executive producer, Ellica Rowen ; script, Douglas L. Lieberman, Mel Waskin
Keywords: Chemical kinetics; Chemical reactions; Equilibrium